Genetic Modification of Cytokine Signaling to Enhance Efficacy of CAR T Cell Therapy in Solid Tumors - Ghahri-Saremi, Navid; Akbari, Behnia; Soltantoyeh, Tahereh; Hadjati, Jamshid; Ghassemi, Saba; Mirzaei, Hamid Reza (Frontiers in Immunology, 2021)
Chimeric antigen receptor (CAR) T cell therapy has shown unprecedented success in treating advanced hematological malignancies. Its effectiveness in solid tumors has been limited due to heterogeneous antigen expression, a suppressive tumor microenvironment, suboptimal trafficking to the tumor site, and poor CAR T cell persistence. Several approaches have been developed to overcome these obstacles through various strategies including the genetic engineering of CAR T cells to blunt the signaling of immune inhibitory receptors as well as to modulate signaling of cytokine/chemokine molecules and their receptors. In this review, we offer our perspective on how genetically modifying cytokine/chemokine molecules and their receptors can improve CAR T cell qualities such as functionality, persistence (e.g. resistance to pro-apoptotic signals), and infiltration into tumor sites. Understanding how such modifications can overcome barriers to CAR T cell effectiveness will undoubtedly enhance the potential of CAR T cells against solid tumors.